High speed flow measurement devices for gasoline fuel injectors - Malladi, MRNVLN (2021)
Internal combustion engines (ICEs) are currently widely used in the transport sector, and there are increasingly stringent regulations on pollution from vehicles, such as carbon dioxide (CO2), nitrogen oxides (NOx) and particulate matter (PM). To meet these standards, efficiency improvements in ICEs are being made while limiting exhaust emissions by improving engine control, monitoring and management. Knowledge of mass injected in individual injections taken cycle-by-cycle and cylinder-by-cylinder in an engine can aid in delivering enhanced injector control for engine monitoring, performance and modelling to help achieve these efficiency improvements and limit emissions. Currently, there are no real-time and on-engine direct mass measurements of fuel flow in individual cylinders of an engine due to the lack of appropriate measurement techniques. To achieve this, in this thesis two potential solutions: pressure methods (One Pressure Transducer Method (OPTM) and Two Pressure Transducer Method (TPTM)) and direct measurement of mass flow rate using a Coriolis flowmeter (CFM) (Fast Next Generation Coriolis (FNGC)), were evaluated for future on-engine applications.